PENGARUH KECUKUPAN MODAL, RISIKO KREDIT, EFISIENSI OPERASIONAL, LIKUIDITAS, DAN KEMAMPUAN PENGELOLAAN ASET PRODUKTIF TERHADAP PROFITABILITAS PERBANKAN - Miswanto Miswanto; Talentia Herri Christiana; Meidi Syaflan (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
The purpose of this study is to test whether capital adequacy, credit risk, operational efficiency, liquidity, and productive asset management ability affect the profitability of banks listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The data analysis technique used multiple linear regression panel data. The sample consisted of 22 commercial banks with 110 observations, which were carried out by purposive sampling. Based on the existing test equipment, the estimation model chosen is the random effect model. The results of the analysis show that CAR does not affect ROA, NPL and BOPO have a negative effect on ROA, LDR has no effect on ROA, and NIM has a positive effect on ROA. Therefore, the findings of this study are as follows. First, capital adequacy does not have a positive effect on profitability. Second, credit risk negatively affects profitability. Third, operational efficiency has a positive effect on profitability. Fourth, liquidity does not positively affect profitability. Fifth, the ability to manage productive assets has a positive effect on profitability. This research implies that if banks want to increase profitability, they need to reduce non-performing loans (NPL), lower the BOPO ratio, and increase the NIM.